Left ventricular rotational abnormalities following successful kidney transplantation—insights from the three-dimensional speckle-tracking echocardiographic MAGYAR-Path Study - Borda, Bernadett (Quant Imaging Med Surg, 2018)
BACKGROUND: Kidney transplantation (KTx) is the preferred treatment for virtually all suitable candidates with end-stage renal disease. There is limited information on left ventricular (LV) rotational mechanics post-KTx, therefore the present study aimed to assess it and to compare it to that of age- and gender-matched healthy controls. METHODS: The present study comprised 42 KTx patients, from which 4 patients were excluded due to insufficient image quality (mean age: 46.3±8.2 years, 29 males). Control group consisted of 81 age- and gender-matched healthy individuals (mean age: 43.5±10.8 years, 51 males). All KTx patients and healthy controls successfully underwent transthoracic two-dimensional (2D) Doppler echocardiography and three-dimensional speckle-tracking echocardiography (3DSTE). RESULTS: Significant differences could be demonstrated in LA diameter, LV end-diastolic diameter and volume, interventricular septum, LV posterior wall thickness, LV ejection fraction and early and late filling transmitral flow velocities and in their ratio between KTx patients and controls; none of the subjects examined showed grade 2–4 mitral and/or tricuspid regurgitations. Three patients following successful KTx showed near absence of LV twist called as LV ‘rigid body rotation’ (RBR) movement. When the remaining 35 post-KTx patients were analysed separately, reduced basal LV rotation could be demonstrated in post-KTx patients with tendentious increase in apical LV rotation resulting in an unchanged LV twist. CONCLUSIONS: KTx is associated with alterations in LV rotational mechanics with unchanged LV twist suggesting a remodelling of this sort of movement. The near absence of LV twist (LV-RBR) could be demonstrated in some post-KTx cases.